A parametric study of phase change material behaviour when used with night ventilation in different climatic zones. (January 2019) - Solgi, Ebrahim; Hamedani, Zahra; Fernando, Ruwan; Mohammad Kari, Behrouz; Skates, Henry
Abstract: Night ventilation (NV) is a productive passive cooling technique which demonstrates a high potential for reducing cooling loads and improving thermal comfort; however, its efficiency is highly contingent upon such factors as thermal energy storage. In the current building industry where utilizing lightweight structures is of paramount importance, the usage of Phase Change Materials (PCMs) as efficient lightweight thermal energy storage for NV is becoming rapidly prevalent. Although the effects of the independent variables of NV and PCMs are well-known, their interrelationship has not been clearly established. This study therefore set out to explore the correlation between PCM quantity and transition temperatures, as well as NV airflow and delta temperature, thermal insulation and the resulting energy saving. To do so, a model, validated utilizing a full-scale calorimeter, was employed for numerical simulations of three different climates. It was found that in tropical climates, coupling NV with PCMs was non-effective. Nevertheless, in sub-tropical and hot-dry climates, cooling thermostat set-points, as well as thermal insulation play a key role in defining the optimal PCM temperature utilized for NV. The optimal transitional temperature, however, is not dependent on the PCM thicknesses, but thickening PCMs raises energy saving. The use of well-insulated envelopes increases NV efficiency and stabilizes the optimal PCM transition temperature, defined as 1 °C lower than the cooling set-point temperature. It is also concluded that the importance of thermal insulation in raising NV efficiency is greater than PCM volume. Furthermore, low delta temperature and high airflow result in increasing NV efficiency; however, these phenomena have no effect on the optimal PCM meting temperature. Highlights: A model validated using a full-scale calorimeter is utilized through automation. The importance of insulation thicknesses in raising NV efficiency is greater than PCM thicknesses. Cooling thermostat set-points and thermal insulation play a key role in defining the optimal PCM utilized for NV. NV with low delta temperatures and high airflows is highly efficient. The use of NV coupled with PCMs in tropical climates is non-effective.